Acceptance of Family Planning Methods Among the Married Male of A Selected Rural Area in Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
This descriptive study was conducted in Darogarchala, Sreepur Upazilla with a view to assessing the acceptance of contraceptive methods among the married male. Total 325 participants of age ranging from 20 to 60 years were interviewed. The mean age of the respondents was 38.5 years. Maximum 107 (33%) were in the age group of 30 to 39 years. Majority of the respondents (34%) were illiterate. Among the rest, 91 (28%) had primary education, 87 had completed SSC and 26 had completed HSC and 5 were graduate. In the study, it was found that, majority respondents (34%) were businessmen, 20% were laborers, 19% were service holders, 16% were farmers, and 12% were unemployed. More than 98% of the respondents were muslims. Majority 211 (65%) of the family were nuclear family and 114 (35%) were family from joint family. According to monthly income, it was found that, 141 had monthly income in between 1000 taka to 5000 taka, 110 respondents had income in between 5001 to 10000 taka, 33 had income in between 10001 to 15000 taka, 22 had income between 15001 to 20000 taka, and 10 had income between 20000 to 30000 taka. Only a small fraction (2.54%) earned more than 30000 taka. Maximum (45%) of the respondents were married between the ages 22 to 24 years. According to number of children, majority of the respondents (74.69%) had 1 to 3 alive children and 73.23% wished to have children in the future. 97 of the respondents obtained information from health workers and about 40% from Radio or TV. Most of the respondents (66%) did not use any method of family planning and 33.66% applied one of the family planning methods. Majority (99.02%) used temporary methods of family planning. Only one used permanent method. It revealed that 90.85% did not face any complications and only 9.15% faced difficulties during the use of contraceptives.Chatt  Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 49-52